Nilai-Nilai Pendidikan Karakter dalam Novel Islammu adalah Maharku Karya Ario Muhammad, PhD (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
Literary works are divided into three types, namely prose, poetry, and drama. Prose consists of two types, namely novels and short stories. This literary work called a novel is a type of writing that is very popular. The novel Islammu adalah Maharku by Ario Muhammad, PhD, is a novel that tells about the conflicts of life that are packed with islamic nuances in every problem solving. This research aims to describe the values ​​of character education in the novel Islammu adalah Maharku by Ario Muhammad, PhD. The method used in this study is a qualitative descriptive method. Data collection was carried out using thesee method with the read-note technique. The character education values contained in novel entitled Islammu adalah Maharku by Ario Muhammad, PhD including 1) religious, 2) honest, 3) responsible, 4) disciplined, 5) hardwork, 6) independent, 7) friendly and communicative, 8) care, 9) tolerance, 10) curiosity, 11) love to read, 12) appreciate achievement. By reading novel Islammu adalah Maharku, student will get several benefits, one of which is that can enjoy interesting stories that contain many lessons about life.